2011
DOI: 10.1177/1044207311394853
|View full text |Cite
|
Sign up to set email alerts
|

Postcommunist Deinstitutionalization of Children With Disabilities in Romania

Abstract: The author examines the policies and treatment of children institutionalized during and after the communist regime, the adoption policies for these children, the human rights claimed in the name of these children, and the ecology of disabilities in Romania. Institutionalized children fell into three categories: children who had one or more minor to severe disabilities, children who had been abandoned, and children who were part of ethnic minorities, especially the Roma. The author reviews the literature on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…On the one hand, some countries have been developing and implementing deinstitutionalisation strategies and progressive legal capacity legislation (Kozma and Petri 2012). On the other hand, evidence has demonstrated that merely symbolic legal adaptations have repeatedly failed to realise meaningful changes in actual policy and practice (Kozma and Petri 2012;Phillips 2012;Turnpenny et al 2018;Walker 2011).…”
Section: The European Union and Deinstitutionalisation In The Postsocmentioning
confidence: 99%
“…On the one hand, some countries have been developing and implementing deinstitutionalisation strategies and progressive legal capacity legislation (Kozma and Petri 2012). On the other hand, evidence has demonstrated that merely symbolic legal adaptations have repeatedly failed to realise meaningful changes in actual policy and practice (Kozma and Petri 2012;Phillips 2012;Turnpenny et al 2018;Walker 2011).…”
Section: The European Union and Deinstitutionalisation In The Postsocmentioning
confidence: 99%